THE EFFECT OF SELF EFFICACY, PARENTS ATTENTION AND PEERS SOCIAL SUPPORT TOWARDS STUDENT LEARNING MOTIVATION ON STUDENT - Maghfirah, Izzata; Wolor, Christian Wiradendi; Sariwulan, Rd. Tuty (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this research is getting a valid knowledge about the problems formulated regarding the effect of self-efficacy, parental attention and peer social support on learning motivation in students of SMK Negeri 31 Jakarta. The research method used by the researcher is quantitative, while the total population is 204 students. The sample technique used simple random sampling, which amounted to 135 students obtained from the results of the calculation of the Slovin formula above with an error rate of 5%. Collecting data using a questionnaire by utilizing the google form. Based on the test results of the determinant coefficient analysis, it is known that the R square in the summary model is 0.623. It was concluded that 62.3% was the effect of self-efficacy variables, parental attention and peer social support together on student learning motivation, while the remaining 37.7% was influenced by other factors not examined in this study.